Effects of pocket shape and ignition slot locations on the combustion processes of a rotary engine fueled with natural gas. (5th October 2015) - Fan, B.W.; Pan, J.F.; Pan, Z.H.; Tang, A.K.; Zhu, Y.J.; Xue, H.
Abstract: This work aims to numerically study the performance, combustion and emission characteristics of a side-ported natural-gas-fueled rotary engine under different pocket shapes and ignition slot positions. Simulations were performed using multi-dimensional software FLUENT 14.0. On the basis of the software, a three-dimensional dynamic simulation model was established by writing dynamic mesh programs and choosing a detailed reaction mechanism. The three-dimensional dynamic simulation model, based on the chemical reaction kinetics, was also validated by the experimental data. Simulation results showed that a bigger intensity of the tumble, a larger area of the high speed oblique flow and a higher average flow speed in the middle of the combustion chamber can make the flame propagation speed increase. When the combustion chamber configuration had a middling pocket coupled with an ignition slot located at the middle of the width direction of rotor surface, the combustion rate is the highest. As a result, the cylinder pressure and the intermediate OH increased significantly. Compared with the combustion chamber configuration, which had a flat-top pocket without ignition slot, it showed a 10 percent increase in the peak pressures, but a certain increase in NO emissions. Highlights: A three-dimensional simulation model based on the chemical reaction kinetics was established. The pocket shape of rotor and the position of a new-designed ignition slot is optimized. The tumble and the high speed oblique flow near the TSP is beneficial for combustion rate. The optimal scheme is a middling pocket with an ignition slot located at the middle of rotor surface.